Clinical significance of serum S100 calcium‐binding protein A4 in idiopathic pulmonary fibrosis. Issue 7 (9th October 2019) - Akiyama, Norimichi; Hozumi, Hironao; Isayama, Takuya; Okada, Jun; Sugiura, Katsunori; Yasui, Hideki; Suzuki, Yuzo; Kono, Masato; Karayama, Masato; Furuhashi, Kazuki; Enomoto, Noriyuki; Fujisawa, Tomoyuki; et al.
ABSTRACT: Background and objective: Idiopathic pulmonary fibrosis (IPF) is a progressive interstitial lung disease with a poor prognosis. There are no established serum biomarkers for predicting the outcomes of IPF. S100 calcium‐binding protein A4 (S100A4) is considered as a marker of fibroblasts; however, its clinical application remains to be investigated. We evaluated the clinical relevance of S100A4 in IPF patients. Methods: Serum S100A4 levels in 95 consecutive IPF patients and 50 healthy controls (HC) were measured using enzyme‐linked immunosorbent assay. S100A4 expression in lung tissues was determined using immunohistochemistry/immunofluorescence and its association with disease progression (defined as deterioration in lung function or death) and mortality was assessed using Kaplan–Meier method and Cox hazards analysis. Results: Serum S100A4 levels were undetectable in all HC but were detectable in 26 (27.3%) of the 95 IPF patients ( P  < 0.01). Immunostaining of lung tissues from IPF patients showed aggregation of numerous S100A4‐expressing cells around the fibroblastic foci and mature fibrotic regions. IPF patients with higher serum S100A4 levels had a significantly worse prognosis than those with low serum levels (2‐year cumulative survival rate: 41.7% vs 77.0%, respectively, P  < 0.01). On multivariate analyses, baseline serum S100A4 levels (per 10 ng/mL increase) were independently associated with higher disease progression rate (odds ratio: 1.06, P = 0.01) and higher mortality (hazard ratio: 1.18, P = 0.03). Conclusion: S100A4 is a promising serum biomarker that may help predict disease progression/mortality. Our findings may help establish treatment strategies for IPF. Abstract : S100 calcium‐binding protein A4 is a promising serum biomarker that may predict disease progression and mortality in idiopathic pulmonary fibrosis (IPF) patients. Insights from this study may facilitate establishment of treatment strategies for IPF. See related  Editorial